2004
DOI: 10.1016/s0002-9440(10)63343-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of 25-Hydroxyvitamin D-1α-Hydroxylase in Dysgerminomas

Abstract: Humoral hypercalcemia of malignancy (HHM) is a common paraneoplastic disorder usually associated with increased synthesis of parathyroid hormone-related peptide (PTHrP). Unlike non-cancer forms of hypercalcemia, HHM does not routinely involve increased circulating levels of the active form of vitamin D, 1,25-dihydroxyvitamin D3 (1,25(OH)2D3). Dysgerminomas are a notable exception to this rule, previous reports having described hypercalcemia with elevated serum 1,25(OH)2D3. To investigate the etiology of this f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 46 publications
7
51
0
2
Order By: Relevance
“…This study thus provided a clear demonstration of the dependence of immune responses on circulating 25D levels. Similarly, stimulation of the TLR4/ CD14 receptor complexes by lipopolysaccharide induces CYP27B1 expression (84; unpublished results), consistent with correlations that other workers have found between TLR4 and CYP27B1 expression (27,28).…”
Section: Vitamin D Signaling and Metabolism In The Immune Systemsupporting
confidence: 87%
“…This study thus provided a clear demonstration of the dependence of immune responses on circulating 25D levels. Similarly, stimulation of the TLR4/ CD14 receptor complexes by lipopolysaccharide induces CYP27B1 expression (84; unpublished results), consistent with correlations that other workers have found between TLR4 and CYP27B1 expression (27,28).…”
Section: Vitamin D Signaling and Metabolism In The Immune Systemsupporting
confidence: 87%
“…3D) data may reflect inherent differences in 1a-hydroxylase transactivation: recent studies have characterized polymorphisms within the gene for 1a-hydroxylase (CYP27B1), which may confer variability in the regulation of 1a-hydroxylase expression (47). The underlying basis for up-regulation of 1a-hydroxylase in breast tumors is also clear, but we have observed a similar induction of 1a-hydroxylase in lymphomas (37) and dysgerminomas (48). In these cases, synthesis of 1,25(OH) 2 D 3 was mediated via expression of 1a-hydroxylase in tumor-associated macrophages, and a similar pattern of increased expression of 1a-hydroxylase has also been reported in alveolar macrophages associated with lung cancer (49).…”
Section: Vitamin D Metabolism In Breast Cancermentioning
confidence: 55%
“…Since the patient described here was pregnant and had no phenotypical signs that would suggest relevant syndromic data, she was not asked about, or assessed for, this possibility. An association between dysgerminoma and malignant hypercalcemia 10,18,19 has been described by some authors, but in this case tests showed that the patient was within normal limits. Another peculiarity that attracts attention is the association with dysgerminoma described in some varieties of animals 20,21 .…”
Section: Imaging In Medicine Introductionmentioning
confidence: 57%